PENGARUH PERSEPSI HARGA, CITRA MEREK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN - Iqbal, Muhammad; Chodidjah, Suryani (LPPM Universitas Asa Indonesia, 2025)
This study aims to analyze the influence of price perception, brand image, and promotion on the purchasing decisions of Es Teh Indonesia consumers at TB. Simatupang. The research used a quantitative approach with a survey method by distributing questionnaires to 100 respondents selected through purposive sampling based on criteria relevant to the research objectives. Data were analyzed using multiple linear regression to identify partial and simultaneous effects of the three independent variables on the dependent variable, namely consumer purchasing decisions. The results show that price perception, brand image, and promotion jointly have a significant influence on purchasing decisions. Partially, each variable also has a positive and significant effect. Among these variables, promotion is the most dominant factor in driving purchasing decisions, as it can attract attention, create interest, provide clear information, build emotional connections, foster strong trust, and increase the likelihood of repeated purchases consistently and sustainably in the future